Perceived social support, insomnia, and psychological resilience: a chain mediation model of internet addiction in civil aviation cadets - Chen, Wenjia; Zhao, Bochuan; Tu, Haining; Liao, Mingyu; Zhang, Xinan; Su, Yuqi (Frontiers in Psychiatry, 2025)
PurposeBased on the stress-vulnerability model and protective-risk model, this study examines the mechanism by which perceived social support affects internet addiction among civil aviation flight cadets, focusing on testing the chain mediating role of insomnia and psychological resilience.MethodsUsing a cross-sectional questionnaire survey, 1218 flight cadets (mean age approximately 18.8 years) were recruited through convenience sampling from a civil aviation flight college in China. Participants completed the Perceived Social Support Scale (PSS), Athens Insomnia Scale (AIS), Connor-Davidson Resilience Scale (CD-RISC), and Chinese Internet Addiction Scale-Revised (CIAS-R). Chain mediation analysis was performed using SPSS PROCESS macro Model 6 (Bootstrap resampling 5000 times, 95% confidence interval).ResultsSignificant correlations were found between all pairs of variables: perceived social support, insomnia, psychological resilience, and internet addiction (p < 0.01). Perceived social support was significantly negatively correlated with internet addiction (r=-0.34) and insomnia (r=-0.26), while significantly positively correlated with psychological resilience (r=0.65); insomnia was significantly positively correlated with internet addiction (r=0.30); psychological resilience was significantly negatively correlated with internet addiction (r=-0.44). Chain mediation analysis showed that perceived social support not only directly negatively predicted flight cadets’ internet addiction but also had indirect effects through insomnia and psychological resilience: on one hand, perceived social support indirectly reduced internet addiction by decreasing insomnia (r=-0.05); on the other hand, perceived social support indirectly reduced internet addiction by increasing psychological resilience (r=-0.21); additionally, perceived social support indirectly affected internet addiction through the chain mediating path of first reducing insomnia and then increasing psychological resilience (r=-0.01), and although the effect size of this chain mediation was small, it reached a significant level.ConclusionPerceived social support has a significant inhibitory effect on internet addiction among civil aviation flight cadets, with insomnia and psychological resilience playing a partial chain mediating role. Enhancing flight cadets’ social support, improving their sleep status, and strengthening psychological resilience may alleviate the risk of internet addiction.